Quality of Work Life of the Regular Full Time Faculty Members of the Private Autonomous Business Schools of Bengaluru, India: A Study - Dr. Indranil Bose, Dr. Jayanta Banerjee (International Journal of Advanced Science and Technology, 2020)
Quality of work-life is fast becoming an important determinant of employee productivity and performance across industries. Teaching profession is no exception to this phenomenon. The present study is however an attempt to analyse the perception of the selected B-school faculty members with regard to Quality of Work Life. The data has been collected with the help of a structured questionnaire from one hundred ten regular faculty members of five private business schools offering autonomous PGDM programmes in and around Bengaluru The study has excluded government university business management departments as some of the previous studies have already addressed the issue of Quality of Work Life of the regular faculty members of such departments. The study has dealt with fifteen dimensions of Quality of Work-life (each having sub-factors). The respondents have been categorized on the basis of age and qualification for the purpose of analysis. The Cronbach’s Coefficient Alpha has been applied to check the reliability of the variables. Standard statistical tools like Mean, Standard Deviation and ANOVA have been used to analyses the data. The results of the study shows that no significant perceptual difference exists with regard to the dimensions of Quality of Work-life in relation to age and qualifications. The present study has further highlighted the areas of dissatisfaction among the respondents as well.